Fronteiras corpóreas e incorporações prisionais - Cunha, Manuela Ivone (2019)
This paper compares materials drawn from fieldwork in a prison before and after the rise of concentrated incarceration that tightly interlocked it with a handful of urban neighborhoods. As these worlds became continuous, former intra-prison boundaries collapsed, entailing changes that included corporeal and sensorial aspects of prison experience. The imprisoned body is described not as a bounded object of disciplinary power but as constituted first and foremost by social and moral relations, rendering bodily experiences of confinement highly contextual. A comparison between forms more and less shaped by a particular prison-urban relation suggests that these experiences vary according to prison-specific circumstances, but also to social-specific circumstances.